The Tenebrionidae Latreille, 1802 (Coleoptera: Tenebrionoidea) of the Philippines. Part 2. Two new species of the genus Gauromaia Pascoe, 1866 (Cnodalonini) from Mindanao Island - Medina, Milton Norman; Cabras, Analyn; Ruzzier, Enrico (Zootaxa, 2022)
In the present contribution two new species of the genus Gauromaia (Tenebrionidae: Cnodalonini), namely G. ruffordi sp. nov. and G. kitangladensis sp. nov. from the island of Mindanao (Philippines) are described and illustrated.